Smart and Sustainable Technology for Resilient Cities and Communities - Howlett, Robert J.; Jain, Lakhmi C.; Littlewood, John R.; Balas, Marius M. (Advances in Sustainability Science and Technology, 2022)
XVI, 322 p. 106 illus., 89 illus. in color.